A Study on the Development of a Korean Metabolic Syndrome Questionnaire Using Blood Stasis Clinical Data. (27th May 2019) - Kang, Byoung-Kab; Jang, Soobin; Ko, Mi Mi; Jung, Jeeyoun
Abstract : Objective . The aims of this study were to extract clinical indicators related to metabolic diseases using the Blood Stasis Questionnaires I and II (BSQ-I and II) developed in 2013 and 2014, respectively, and to develop a BSQ on metabolic syndrome (BSQ-MS). Methods . A total of 2, 158 patients, comprising 1, 214 from 7 traditional Korean medical hospitals in 2013 and 944 from 3 traditional Korean medical hospitals in 2014, were asked to complete the BSQ-I and BSQ-II. For the 370 patients who met the metabolic syndrome criteria, reliability and validity of the BSQ-MS were assessed using Cronbach's alpha, while prediction accuracy was determined by logistic regression. Results . The BSQ-MS included a total of 15 clinical signs and symptoms. It showed satisfactory internal consistency (Cronbach's α coefficient=0.70) and validity, with significant differences in mean scores between the blood stasis (14.09±6.14) and non-blood stasis (9.09±5.60) subject groups. The cut-off value of BSQ-MS score was 9 points, the area under the receiver operating characteristic curve was approximately 77%, the sensitivity and specificity of the diagnostic accuracy according to the cut-off value were 82.9% and 49.7%, respectively, and the sensitivity and specificity of the prediction accuracy by logistic regression were 72.2% and 71.6%, respectively. Conclusion . These results suggest that the BSQ-MS is an appropriate instrument for estimating blood stasis in patients with metabolic syndrome, although its sensitivity for diagnosis according to the cut-off value is low.